Fusarium spp. associated with carnation (Dianthus caryophyllus L.) in Baja California, Mexico - Camacho López María Dolores; Valenzuela Solano César; Hernández Martínez Rufina (Revista Mexicana de Ciencias Agrícolas, 2018)
Carnation is an ornamental species of great economic importance worldwide. In the State of Baja California, Mexico, there are no records of Fusarium spp. associated with damage or disease in carnation plants, therefore this study aimed at morphological and molecular identification of Fusarium spp. strains isolated from plants with wilt symptoms. Forty two fungal strains were isolated and based on the morphological characteristics evaluated on PDA, SNA and CLA culture media, and phylogenetic analysis of EF1α sequences, the following species were identified: Fusarium oxysporum, F. proliferatum, F. solani, F. tricinctum, F. globosum, F.incarnatum and F. equiseti. The F. oxysporum species prevailed in all collection sites and F. tricinctum, F. solani and F. globosum are first reported associated with carnation in Mexico.